Dynamic instability of variable stiffness composite plates - Loja, Amélia (2017)
Due to its tailorability intrinsic characteristics, composite materials are an effective option in structural design or on its reengineering, especially when the ratios stiffness and/or strength to weight are relevant. Dual-phase or multiphase fibre reinforced composites can thus be found in many engineering and science applications. However, in the majority of the cases these composites are made from unidirectional plies stacking. The possibility of building fibre reinforced composite structures, wherein these fibres follow curvilinear paths, may be an important enhancement to structural mechanical response and in particular to its dynamic stability, as variable fibre orientation is responsible for variable elastic stiffness within a generic layer. This work aims characterizing the dynamic instability response of variable stiffness composite plates, according to different material and geometrical parameters. To this purpose one considers Rayleigh-Ritz method to perform buckling, free vibrations and dynamic instability analyses, using orthogonal polynomials. The dynamic instability problem is solved considering Bolotin's method. A set of verification and illustrative case studies is considered and discussed.